Unstable Tandem Repeats in Promoters Confer Transcriptional Evolvability - Vinces, Marcelo D. (2009)
Relative to most regions of the genome, tandemly repeated DNA sequences display a greater propensity to mutate. A search for tandem repeats in the Saccharomyces cerevisiae genome revealed that the nucleosome-free region directly upstream of genes (the promoter region) is enriched in repeats. As many as 25% of all gene promoters contain tandem repeat sequences. Genes driven by these repeat-containing promoters show significantly higher rates of transcriptional divergence. Variations in repeat length result in changes in expression and local nucleosome positioning. Tandem repeats are variable elements in promoters that may facilitate evolutionary tuning of gene expression by affecting local chromatin structure.